Pelatihan Kreativitas Limbah Non Organik pada Anggota PKK RW 10 Kelurahan Tapos Kota Depok - Oktaviana, Eva; Ulfa, Maria; Hasanah, Nur (LPPM Universitas Flores, 2023)
The purpose of this service is to develop the creativity of PKK RW 10 Tapos District Depok City members regarding non-organic waste processing, in addition to providing entrepreneurial motivation training, non-organic product manufacturing training, online media marketing training, and assistance to participants in non-organic waste processing training. The background for this activity is because there is an accumulation of waste in Depok, each Depok resident produces an average of 0.67 litres of waste per day. So that is the reason for holding training on utilising non-organic waste into products that have a sale value. To reduce the disposal of waste made from plastic and glass bottles. The methods used in this service are lecture, practice and demonstration methods. The techniques used are planning, implementation, mentoring and evaluation. The products produced at this PKM are 1) home decorations from syrup bottles, and woven bags from the rim of plastic drinking glasses, besides that motivation in making products from quality waste and online marketing (shopee).